2006
DOI: 10.1007/s10620-006-9351-6
|View full text |Cite
|
Sign up to set email alerts
|

Results of Videocapsule Endoscopy ∊ 250 Patients With Suspected Small Bowel Pathology

Abstract: We aimed to assess technical feasibility, clinical applicability, and diagnostic yield of videocapsule endoscopy (VCE) in a large group of unselected patients. VCE was performed with the Given Imaging swallowable capsule. Findings were considered diagnostic if the observed finding could explain the symptomatology of the patient. Findings were considered suspicious if an observed finding failed to completely explain the patient's symptoms. We studied 250 patients. A definite diagnosis was made in 95 patients (3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 35 publications
1
26
0
Order By: Relevance
“…The main characteristics of the studies eligible for review are shown in Table 1. Five studies were from the United States, 22 15,16 and the Netherlands, 19,29 and 1 study each from Australia, 34 India, 32 Israel, 13 Japan, 35 Norway, 18 Spain, 20 and the United Kingdom. 25 Seven of them were prospective 15,20,21,28,[33][34][35] and 17 were retrospective studies.…”
Section: Descriptive Assessment and Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main characteristics of the studies eligible for review are shown in Table 1. Five studies were from the United States, 22 15,16 and the Netherlands, 19,29 and 1 study each from Australia, 34 India, 32 Israel, 13 Japan, 35 Norway, 18 Spain, 20 and the United Kingdom. 25 Seven of them were prospective 15,20,21,28,[33][34][35] and 17 were retrospective studies.…”
Section: Descriptive Assessment and Study Characteristicsmentioning
confidence: 99%
“…25 Seven of them were prospective 15,20,21,28,[33][34][35] and 17 were retrospective studies. [12][13][14][16][17][18][19][22][23][24][25][26][27][29][30][31][32] Only 2 were multicenter studies. 12,13 In all but 4 studies (in 3, not reported 18,23,27 and 1 study 31 with EndoCapsule [Olympus, Tokyo, Japan]), SBCE explorations were performed with capsule endoscopes from Given Imaging Ltd (Yoqneam, Israel).…”
Section: Descriptive Assessment and Study Characteristicsmentioning
confidence: 99%
“…Some studies have demonstrated abnormal findings in more than one third of patient examinations, with an even higher yield in patients with suspected CD. 2,3 Although the yield of CE may be high, many of the abnormalities detected are not specific for CD. Minor mucosal abnormalities can be observed in almost one fifth of asymptomatic individuals 4 and in as many as two thirds of individuals regularly using nonsteroidal anti-inflammatory drugs (NSAIDs).…”
Section: Role Of Ce In Suspected CDmentioning
confidence: 99%
“…In the past few years several studies have shown that WCE is indeed a patient-friendly investigation and is clinically useful [16][17][18][19][20]. A disadvantage of WCE in CD patients is the risk of capsule retention, which has been reported in up to 7% of CD patients.…”
Section: Discussionmentioning
confidence: 99%